Pseudopancreatic Cyst Extending into the Mediastinum in a 7-Year-Old Child - Mostafa Kotb; Ahmed Oshiba; Khaled Ashour (Georg Thieme Verlag KG, 2019)
Mediastinal pseudopancreatic cyst (MPP) is the extension of a pancreatic pseudocyst through esophageal or aortic hiatus into the posterior mediastinum. It can produce a range of manifestations caused by compression by the cyst, for instance, odynophagia, dysphagia, pericardial, or pleural effusion. Here we report a case of MPP in a 7-year-old child who was presented with repeated chest infections and left pleural effusion. It was successfully drained by cystogastrostomy.